On a hexactinellid sponge aggregation at the Great Meteor seamount (North-east Atlantic) - Xavier, J.R.; Tojeira, I.; Van Soest, R.W.M. (Journal of the Marine Biological Association of the United Kingdom, 2015)
Hexactinellids or glass sponges constitute a predominantly deep-sea sponge group typically occurring at bathyal and abyssal depths. Some species form dense populations along the European and African continental slope but the distribution and extent of these populations remains ill known and the driving factors behind their occurrence poorly understood. Here we report an aggregation of the hexactinellid sponge Poliopogon amadou Thomson, 1878 at 2700 m depth on the Great Meteor seamount, a large seamount located southern of the Azores archipelago. A description of the species, along with scanning electron microscopy of its spicules, is provided.